Analisis Dampak Pembangunan Sumur Bor pada Perumahan Subsidi Kemiling Permai 5 - Rezi Munizar; Revva Zamriansyah (Journal of Science, Technology, and Innovation, 2026)
Clean water is a basic necessity that plays an essential role in supporting public health, sanitation, and daily activities. Limited access to clean water in residential areas encourages groundwater utilization through drilled wells as an alternative water supply solution. This study aims to analyze the impacts of drilled well development at Kemiling Permai 5 Subsidized Housing on clean water fulfillment, social, economic, and environmental aspects. This research employed a descriptive qualitative method using observation, interviews, documentation, and literature studies for data collection. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that drilled well development improves clean water availability, community comfort, household economic efficiency, and public participation in facility management. However, sustainable groundwater management is required to maintain water quality and availability while preventing environmental degradation. This study provides insights into the importance of integrating technical, social, and environmental considerations in managing drilled well systems within subsidized residential areas.